Social Networks, Gender Norms and Labor Supply: Experimental Evidence Using a Job Search Platform - Farzana Afridi; Amrita Dhillon; Sanchari Roy; Nikita Sangwan (Queen's University Belfast, Queen's Business School, 2025)
This paper studies the role of job search frictions and gender norms in shaping intrahousehold labor market outcomes in developing countries. We conduct a field experiment in Delhi, India where we randomly offer access to a hyper-local digital job search and matching platform either to married couples only (non-network treatment), or together with the wife's peer network (network treatment), or not at all. Approximately one year later, we find that couples in the non-network treatment group exhibit a degree of substitution in labor supply - wives reduce their intensive margin of work, driven by withdrawal from casual labor, while husbands increase theirs. In contrast, husbands in the network treatment group increase their labor supply on both extensive and intensive margins but with no impact on their wives' labor supply on either margin. Instead, wives' occupational structure shifts towards self-employment in the network treatment group. Our findings can be explained by a simple conceptual framework that incorporates gender-differentiated job search frictions, conservative social norms against (married) women's market work and home-production constraints.
Keywords: J16; J21; J24; O33; 330; social networks; social norms; gender; job-matching platforms; employment